2014
DOI: 10.1007/s00468-014-1003-4
|View full text |Cite
|
Sign up to set email alerts
|

Wood density proxies of adaptive traits linked with resistance to drought in Douglas fir (Pseudotsuga menziesii (Mirb.) Franco)

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…Knowing the vulnerability curves (or the P 50 ) of different species and plant organs is a prerequisite for understanding and predicting mortality patterns. Recent research comparing traits of Pseudotsuga menziesii trees after a severe drought in France showed slightly higher wood densities in the survivors (Ruiz Diaz Britez et al 2014). These results are consistent with research showing that clones of the same species that had higher density also had more negative values of P 50 (Dalla-Salda et al 2009).…”
Section: Transport Safety and Drought-induced Cavitationsupporting
confidence: 90%
“…Knowing the vulnerability curves (or the P 50 ) of different species and plant organs is a prerequisite for understanding and predicting mortality patterns. Recent research comparing traits of Pseudotsuga menziesii trees after a severe drought in France showed slightly higher wood densities in the survivors (Ruiz Diaz Britez et al 2014). These results are consistent with research showing that clones of the same species that had higher density also had more negative values of P 50 (Dalla-Salda et al 2009).…”
Section: Transport Safety and Drought-induced Cavitationsupporting
confidence: 90%
“…Interestingly, these traits measured at branch scale do not map on the same PCA axis than WDens (correlated with PC4), which corresponds to another organization level (trunk). The variation in WDens is expected to be related to the strong within‐ population variation in resistance to stem cavitation observed in Fagus sylvatica (Wortemann et al ), even though the relationship between resistance to cavitation and WDens at intra‐population level remains to be proven in this species (as in Ruiz‐Diaz‐Britez et al for Pseudostuga menziesii ). Finally, N mass behaves quite independently from the other traits and from LMA in particular, in opposition with the observations made by interspecific studies (Wright et al ) but in agreement with other intraspecific studies (Laforest‐Lapointe et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown a strong connection between drought resistance and wood anatomy, such as the diameter of vessel or tracheids, and adaptive tree growth reduction in response to changes in soil water potential (Kannenberg et al, ; Pellizzari et al, ). Species that occur in both humid and arid environments (e.g., Douglas‐fir trees in montane western landscapes) exhibit high plasticity in number and size of tracheids, which is reflected in wood density as a result of adaptive growth patterns under variable water regimes (Ruiz Diaz Britez et al, ). Thus, the integrated study of structure (e.g., growth and wood formation) and function (e.g., carbon and water flows) of dominant Douglas‐fir trees can help elucidate past and future forest vulnerabilities to climate fluctuations (Voltas et al, ).…”
Section: Introductionmentioning
confidence: 99%